Developing a Model of Participatory Academic Administration to Develop Skills Necessary for the Life and Work of Learners in the 21st Century of Ban Sri than Municipal School Khon Kaen Municipality - Rittiyong, Saisuda (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were 1) to study the basic information, problem conditions and the need to achieve the goal of success in participatory academic administration. To develop the skills necessary for the life and work of learners in the 21st century at Ban Sri Than Municipal School, Khon Kaen Municipality 2) to Develop a participatory academic administration model to develop skills necessary for life. 3) to study the effect of using participative academic administration model to develop skills necessary for learners' life and work; and 4) to evaluate the use of the academic administration model. participatory form to develop skills necessary for the life and work of learners by using research and development methods in 4 steps, namely Research (R1), Development (D1), Research (R2) and Development (D2). The target group and research sample group totaled 298 people, consisting of 1 school administrator, a teacher and Educational personnel 36 people Basic Education Board of Ban Sri Than Municipal School Khon Kaen Municipality consisted of 13 people, 18 parents and 4 community representatives. User Guide and participant observation the data were analyzed by means of mean and standard deviation. The results showed that 1. A study of basic information about the school context. There is a clear development direction that covers all aspects of development. Modern and feasible Opportunities for stakeholders to participate in operations and problem conditions and needs to achieve the goal of success in participatory academic administration to develop skills necessary for the life and work of learners The overall condition of the academic administration with participation was at a moderate level. The areas that gave the most participation were the development of innovative media and technology, and the development of learning resources and local wisdom.